Importance of Implementation of Strategic Control of Enterprises and Organizations of Consumer Cooperatives - Семенів, М. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the article investigational and essence of term "strategic control" is certain. Importance of existence of strategic control is reasonable on enterprises and organizations of consumer co-operation of Ukraine. The location of strategic control is determined in control system by enterprises and organizations of consumer co-operation of Ukraine. The problem of introduction of strategic control is investigational on enterprises and organizations of consumer co-operation. The general model of realization of strategic control is brought around to enterprises and organizations of consumer co-operation.